Industrial Education Impact on Vocational Student Social Skills - Dwiyanti, V.; Ana, Ana; Widianingsih, I. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2018)
Industrial education is a dual system learning between industry and school. In this learning of vocational high school must fulfill industry and school qualification. Industrial education will help student to know and understand industry demand. In disruption and industry revolution 4.0 era more skills must had by them, such as social skills. This research method used literature review to see more resources about industrial education impact on vocational student social skills. And this research result is found two more important social skills. First, adaptability is a skill will help students to know and understand industry work and world, such as how to use technology, follow all industry SOP, all new chalanges industry, etc. Second, communication is an important skills to had. Because it will deliver us to make another understand all massage in verbal and non verbal clearly. They will help student to prepare and face human-robot competition in industry revolution 4.0 in the future.